Circularly Polarized Lasing from a Microcavity Filled with Achiral Single‐Crystalline Microribbons - Liang, Qian; Ma, Xuekai; Long, Teng; Yao, Jiannian; Liao, Qing; Fu, Hongbing (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Quinuclidine-Immobilized Porous Polymeric Microparticles as a Compelling Catalyst for the Baylis–Hillman Reaction - Kumar, Amit; Kuckling, Dirk; Nebhani, Leena (ACS Applied Polymer Materials)
Poly(quinuclidin-3-yl methacrylate-co-divinylbenzene) microparticles having porous as well as nonporous morphology and varying contents of quinuclidine functionality were synthesized by distillation–precipitation polymerization. Further, the synthesized microparticles were explored to catalyze the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Porous and nonporous microparticles functionalized with a catalytic moiety with a loading of 70% (labeled as P70 and NP70) were employed to optimize reaction parameters such as water content, solvent, and temperature for the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Using optimal conditions, the catalytic efficiency of porous and nonporous microparticles at different feed compositions was determined. Porous microparticles containing 70% of quinuclidine (P70) displayed 100% conversion within 16 h at 50 °C, while nonporous microparticles containing 70% of quinuclidine (NP70) displayed a relatively less catalytic conversion, which is attributed to their lower surface area. Furthermore, the catalytic activity of porous microparticles containing 70% of quinuclidine (P70) for the Baylis–Hillman reaction involving a variety of aryl aldehyde derivatives was determined, where the microparticles displayed impressive catalytic efficiency. In addition, the reusability of the microparticles functionalized with a catalytic moiety was evaluated for five cycles of catalytic reaction.
Keywords: distillation−precipitation polymerization; porous microparticles; heterogeneous catalysis Baylis−Hillman reaction; reusable catalyst

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3 Reference Catalyst for CO2 Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Wendholt, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Increasing the metal-to-ligand charge transfer (MLCT) excited state lifetime of polypyridine iron(II) complexes can be achieved by lowering the ligand's π* orbital energy and by increasing the ligand field splitting. In the homo- and heteroleptic complexes [Fe(cpmp)2]2+ (12+) and [Fe(cpmp)(ddpd)]2+ (22+) with the tridentate ligands 6,2’’-carboxypyridyl-2,2’-methylamine-pyridyl-pyridine (cpmp) and N,N’-dimethyl-N,N’-di-pyridin-2-ylpyridine-2,6-diamine (ddpd) two or one dipyridyl ketone moieties provide low energy π* acceptor orbitals. A good metal-ligand orbital overlap to increase the ligand field splitting is achieved by optimizing the octahedricity through CO and NMe units between the coordinating pyridines which enable the formation of six-membered chelate rings. The push-pull ligand cpmp provides intra-ligand and ligand-to-ligand charge transfer (ILCT, LL'CT) excited states in addition to MLCT excited states. Ground and excited state properties of 12+ and 22+ were accessed by X-ray diffraction analyses, resonance Raman spectroscopy, (spectro)electrochemistry, EPR spectroscopy, X-ray emission spectroscopy, static and time-resolved IR and UV/Vis/NIR absorption spectroscopy as well as quantum chemical calculations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Cover Feature: Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives (Chem. Eur. J. 23/2022) - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates - Wicker, Garrit; Zhou, Rundong; Schoch, Roland; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Cover Picture: Sigmatropic [1,5] Carbon Shift of Transient C3 Ammonium Enolates (Angew. Chem. Int. Ed. 31/2022) - Wicker, Garrit; Zhou, Rundong; Schoch, Roland; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Catalytic Properties of High Nitrogen Content Carbonaceous Materials - Lepre, Enrico; Rat, Sylvain; Cavedon, Cristian; Seeberger, Peter H.; Pieber, Bartholomäus; Antonietti, Markus; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Mn(ii) sub-nanometric site stabilization in noble, N-doped carbonaceous materials for electrochemical CO2 reduction - Kossmann, Janina; Sánchez-Manjavacas, Maria Luz Ortiz; Brandt, Jessica; Heil, Tobias; Lopez Salas, Nieves; Albero, Josep (Chemical Communications)
The reported N-doped noble carbonaceous support provides strong stabilization of Mn( ii ) sub-nanometric active sites as well as a convenient coordination environment to produce CO, HCOOH and CH 3 COOH from electrochemical CO 2 reduction.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Constructing Interfacial Boron‐Nitrogen Moieties in Turbostratic Carbon for Electrochemical Hydrogen Peroxide Production - Tian, Zhihong; Zhang, Qingran; Thomsen, Lars; Gao, Nana; Pan, Jian; Daiyan, Rahman; Yun, Jimmy; Brandt, Jessica; Lopez Salas, Nieves; Lai, Feili; Li, Qiuye; Liu, Tianxi; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Pseudo‐Octahedral Iron(II) Complexes with Near‐Degenerate Charge Transfer and Ligand Field States at the Franck‐Condon Geometry - Moll, Johannes; Naumann, Robert; Sorge, Lukas; Förster, Christoph; Gessner, Niklas; Burkhardt, Lukas; Ugur, Naz; Nuernberger, Patrick; Seidel, Wolfram; Ramanan, Charusheela; Bauer, Matthias; Heinze, Katja (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3Reference Catalyst for CO2Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Strübbe, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

Mixed‐Valence Compounds as Polarizing Agents for Overhauser Dynamic Nuclear Polarization in Solids - Gurinov, Andrei; Sieland, Benedikt; Kuzhelev, Andrey; Elgabarty, Hossam; Kühne, Thomas; Prisner, Thomas; Paradies, Jan; Baldus, Marc; Ivanov, Konstantin L.; Pylaeva, Svetlana (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Tricyanidoferrates(−IV) and Ruthenates(−IV) with Non‐Innocent Cyanido Ligands - Jach, Franziska; Wagner, Frank R.; Amber, Zeeshan H.; Rüsing, Michael; Hunger, Jens; Prots, Yurii; Kaiser, Martin; Bobnar, Matej; Jesche, Anton; Eng, Lukas M.; Ruck, Michael; Höhn, Peter (Angewandte Chemie International Edition)
Exceptionally electron-rich, nearly trigonal-planar tricyanidometalate anions [Fe(CN)3]7− and [Ru(CN)3]7− were stabilized in LiSr3[Fe(CN)3] and AE3.5[M(CN)3] (AE=Sr, Ba; M=Fe, Ru). They are the first examples of group 8 elements with the oxidation state of −IV. Microcrystalline powders were obtained by a solid-state route, single crystals from alkali metal flux. While LiSr3[Fe(CN)3] crystallizes in P63/m, the polar space group P63 with three-fold cell volume for AE3.5[M(CN)3] is confirmed by second harmonic generation. X-ray diffraction, IR and Raman spectroscopy reveal longer C−N distances (124–128 pm) and much lower stretching frequencies (1484–1634 cm−1) than in classical cyanidometalates. Weak C−N bonds in combination with strong M−C π-bonding is a scheme also known for carbonylmetalates. Instead of the formal notation [Fe−IV(CN−)3]7−, quantum chemical calculations reveal non-innocent intermediate-valent CN1.67− ligands and a closed-shell d10 configuration for Fe, that is, Fe2−.
Keywords: General Chemistry; Catalysis

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry